56 The value of written information in improving patient experience. (16th November 2020) - Crotty, T; Keane, E; Moran, T; O'Dwyer, TP; Rafferty, M; Khoo, SG
Abstract : Flexible nasendoscopy (FNE) is a common procedure performed in ENT outpatient clinics. Although the majority of patients tolerate the procedure reasonably well, approximately 25% patients find the procedure distressing. Considering written information is cheap and widely accessible, we provided patients with an information leaflet prior to performing FNE and measured their satisfaction using a structured questionnaire. Our results demonstrated a large improvement in patient satisfaction and understanding post-procedure. Additionally, patients found physicians who administered the information leaflet as having explained the procedure more comprehensively than without a questionnaire. As healthcare professionals, we are committed to continually trying to improve patient experience. Providing leadership and innovation in healthcare can seem like a daunting task. However, small, simple changes can often result in large improvements in patient outcome. As leaders, we must increase awareness of the potential implications of small changes, such as written information on patient satisfaction.